2019
DOI: 10.1080/21623945.2019.1595269
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals association of peripheral adipose tissue pathology with type-2 diabetes in Asian Indians

Abstract: Type 2 diabetes (T2D) is a complex disease with an elusive link between its molecular aetiology and clinical presentation. Although, the role of visceral adipose tissue in insulin-resistance and T2D is known, limited information is available on the role of peripheral-subcutaneous adipose tissue especially in Asian Indians. In this microarray-based study of diabetic and normal glucose tolerant Asian Indians, we generated the transcriptome of their thigh adipose tissue and analyzed differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…Keeping in view the fact that diabetics had larger adipocyte size (although statistically insignificant in subcutaneous adipose depot), the modules of co-expressed genes in both depots showed association with its intermediate phenotypic traits and these modules of co-expressed genes enriched inflammation- and adipogenesis-related pathways; all such findings suggest that diabetes is associated with pathologic adipose tissue in both compartments. In two recent studies [ 38 , 62 ], we showed that diabetes is associated with similar pathologic changes in peripheral subcutaneous adipose tissue, and these pathologic changes show an association with diabetes-related intermediate phenotypic traits. Taken together, this evidence explains that the “thin fat” phenotype of Asian Indians is due to qualitative pathologic alterations in the adipose tissue.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Keeping in view the fact that diabetics had larger adipocyte size (although statistically insignificant in subcutaneous adipose depot), the modules of co-expressed genes in both depots showed association with its intermediate phenotypic traits and these modules of co-expressed genes enriched inflammation- and adipogenesis-related pathways; all such findings suggest that diabetes is associated with pathologic adipose tissue in both compartments. In two recent studies [ 38 , 62 ], we showed that diabetes is associated with similar pathologic changes in peripheral subcutaneous adipose tissue, and these pathologic changes show an association with diabetes-related intermediate phenotypic traits. Taken together, this evidence explains that the “thin fat” phenotype of Asian Indians is due to qualitative pathologic alterations in the adipose tissue.…”
Section: Discussionmentioning
confidence: 76%
“…As far as the Asian Indians are concerned, few studies point towards a potential role of subcutaneous abdominal adipose tissue in the pathogenesis of insulin resistance and possibly diabetes [ 37 ], but more studies are lacking. Recently we revealed the association between transcription profiles of peripheral subcutaneous adipose tissue and diabetes-related intermediate phenotypic traits of diabetes [ 38 ]. Whether this fat depot plays a causative or protective role in the pathogenesis of diabetes was not clarified by the study.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, these transcription profiling datasets were furtherer processed using Bioconductor package gcrma [10]. A non-specific filtering step was then carried out to select high sensitivity probes using package genefilter [8]. Differential gene expression was estimated using limma [9].…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 presents gender-wise measured anthropometric, and biochemical parameters. The clinical information with detailed methodology has been published elsewhere [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…We next used human-derived differential expression data of adipose tissue, skeletal muscle and liver which were described in the literature in order test to which extent putative miRNA-mRNA interactions affect mRNA levels. Concerning the gWAT, we evaluated the expression of the 23 upregulated transcripts identified in gWAT of NZO mice with data of adipose tissue of 6 obese non-diabetic, 14 obese diabetic, 16 healthy and 19 diabetic patients 20,21 . Of 23 candidates which exhibit SNPs in miRNA-mRNA binding sites in the human genome, eight showed differential expression, at least in one comparison ( Supplementary Table S5).…”
mentioning
confidence: 99%